Derivatized versus non-derivatized LC-MS/MS techniques for the analysis of estrogens and estrogen-like endocrine disruptors in human plasma - Vitku, J; Horackova, L; Kolatorova, L; Duskova, M; Skodova, T; Simkova, M (Ecotoxicology and environmental safety, 2023)
Bisphenols, parabens, alkylphenols and triclosan are anthropogenic substances with a phenolic group that have been introduced to the environment in recent decades. As they possess hormone-like effects, they have been termed endocrine disruptors (EDs), and can interfere with steroid pathways in organisms. To evaluate the potential impact of EDs on steroid biosynthesis and metabolism, sensitive and robust methods enabling the concurrent measurement of EDs and steroids in plasma are needed. Of crucial importance is the analysis of unconjugated EDs, which possess biological activity. The aim of the study was to develop and validate LC-MS/MS methods with and without a derivatization step for the analysis of unconjugated steroids (estrone-E1, estradiol-E2, estriol-E3, aldosterone-ALDO) and different groups of EDs (bisphenols, parabens, nonylphenol-NP and triclosan-TCS), and compare these methods on a set of 24 human plasma samples using Passing-Bablok regression analysis. Both methods were validated according to FDA and EMA guidelines. The method with dansyl chloride derivatization allowed 17 compounds to be measured: estrogens (E1, E2, E3), bisphenols (bisphenol A-BPA, BPS, BPF, BPAF, BPAP, BPZ, BPP), parabens (methylparaben-MP, ethylparaben-EP, propylparaben-PP, butylparaben-BP, benzylparaben-BenzylP), TCS and NP, with lower limits of quantification (LLOQs) between 4 and 125 pg/mL. The method without derivatization enabled 15 compounds to be analyzed: estrogens (E1, E2, E3), ALDO, bisphenols (BPA, BPS, BPF, BPAF, BPAP, BPZ), parabens (MP, EP, PP, BP, BenzylP) with LLOQs between 2 and 63 pg/mL, and NP and BPP in semiquantitative mode. Adding 6 mM ammonium fluoride post column into mobile phases in the method without derivatization achieved similar or even better LLOQs than the method with the derivatization step. The uniqueness of the methods lies in the simultaneous determination of different classes of unconjugated (bioactive) fraction of EDs together with selected steroids (estrogens + ALDO in the method without derivatization), which provides a useful tool for evaluating the relationships between EDs and steroid metabolism.
Keywords: estron; triclosan; lidé; estrogeny; tandemová hmotnostní spektrometrie; Triclosan; endokrinní disruptory; Nonylphenol; Tandem Mass Spectrometry; Chromatography, Liquid; Humans; Estrone; Benzhydryl Compounds; Paraben; Parabens; benzhydrylové sloučeniny; parabeny; Estrogens; Endocrine Disruptors; Aldosterone; Bisphenol; Estrogen; chromatografie kapalinová